The puzzle of migrant labour shortage and rural labour surplus in China - Knight, J; Quheng, D; Shi, L (University of Oxford, 2010)
The paper examines the contentious issue of the extent of surplus labour that remains in China. China was an extreme example of a surplus labour economy, but the rapid economic growth during the period of economic reform requires a reassessment of whether the second stage of the Lewis model has been reached or is imminent. The literature is inconclusive. On the one hand, there are reports of migrant labour scarcity and rising migrant wages; on the other hand, estimates suggest that a considerable pool of relatively unskilled labour is still available in the rural sector. Yet the answer has far-reaching developmental and distributional implications. After reviewing the literature, the paper uses the 2002 and 2007 national household surveys of the Chinese Academy of Social Sciences to analyse and explain migrant wage behaviour, to predict the determinants of migration, and to examine the size and nature of the pool of potential rural-urban migrants. An attempt is also made to project the rural and urban labour force and migration forward to 2020, on the basis of the 2005 one per cent Population Survey. The paper concludes that for institutional reasons both phenomena are likely to coexist at present and for some time in the future.